A DNA sequence-based identification checklist for Taiwanese chondrichthyans - Straube, Nicolas; White, William T.; Ho, Hsuan-Ching; Rochel, Elisabeth; Corrigan, Shannon; Li, Chenhong; Naylor, Gavin J.p. (Zootaxa, 2013)
In an effort to establish a DNA sequence based checklist of the highly diverse chondrichthyan fauna of Taiwan, we sequenced the mitochondrial NADH2 gene of 257 freshly sampled specimens of Taiwanese chondrichthyans, which were identified to species level by experts in the field. The newly generated sequences were analysed in the context of an already published phylogeny based on NADH2 sequences of chondrichthyans to identify taxonomically interesting lineages as well as enhancing the already published phylogeny with species hitherto not included. Results show a number of noteworthy findings indicating distinct population differences or cryptic diversity and enhance published data with 22 new species not analyzed so far. Our study may be helpful for further taxonomic work on the Taiwanese chrondrichthyan fauna.